Effect of C60 Fullerene on the expression of ERN1 signaling related genes in human astrocytes. Issue 2 (13th March 2013) - Minchenko, D.O.; Prylutska, S.V.; Moenner, M.; Minchenko, O.H.; Prylutskyy, Y.I.; Schütze, C.; Ritter, U.
Abstract The effect of C60 fullerene on the expression levels of genes, related to endoplasmic reticulum stress and cell proliferation, in human astrocytes was investigated. The exposure of human astrocytes to C60 fullerene during 24 or 72 h increases the expression levels of transcription factor E2F8, insulin‐like growth factor binding protein‐2, and tumor suppressor SMAD mRNAs in human astrocytes. At the same time, the expression levels of HSD17B2, PBEF1, HSPB8 mRNA decrease in cells treated with C60 fullerene, being more intense for HSD17B2. Moreover, C60 fullerene increases the proliferation rate of astrocytes. Thus, C60 fullerene affects the expression of genes which control proliferation.